Promoting Fair and Just School Environments: Developing Inclusive Youth. (March 2022) - Killen, Melanie; Rutland, Adam
Incidents of prejudice and discrimination in K–12 schools have increased over the past decade around the world, including the United States. In 2018, more than two-thirds of the 2, 776 U.S. educators surveyed reported witnessing a hate or bias incident in their school. Children and adolescents who experience prejudice, social exclusion, and discrimination are subject to compromised well-being and low academic achievement. Few educators feel prepared to incorporate this topic into the education curriculum. Given the long-term harm related to experiencing social exclusion and discrimination, school districts need to create positive school environments and directly address prejudice and bias. Several factors are currently undermining progress in this area. First, national debates in the United States and other countries have politicized the topic of creating fair and just school environments. Second, the COVID-19 pandemic has interrupted children's and adolescents' education by halting academic progress which has particularly negatively affected students from marginalized and ethnic/racial minority backgrounds. Third, teachers have experienced significant stress during COVID-19 with an increase in anxiety around virtual instruction and communication with parents. Three strategies recommended to address these converging problems include creating inclusive and nondiscriminatory policies for schools, promoting opportunities for intergroup contact and mutual respect, and implementing evidence-based, developmentally appropriate education programs. It is anticipated that these strategies will help to reduce prejudice, increase ethnic and racial identity (ERI), and promote equity, fairness, and justice in school environments.